CULTURAL AWARENESS FOR ENGLISH LEARNERS - Senowarsito, Senowarsito; AB Prabowo, KA (ETERNAL, 2010)
Abstract The purpose of this study is how to enhance cultural awareness for English learners in Indonesia. Culturally, the learners have got accustomed to using Indonesian mind set or Indonesian expression style rather than native English style. The aim of teaching learning language is that learners should have communicative competence. The communicative competence model (Celce-Murcia et al) introduces that the main competence of communicative competence is discourse competence. The discourse competence can be achieved if the learners have socio-cultural competence, linguistic competence and actional competence. It means that teaching English involves not only knowledge of linguistic aspects and speech act or rhetoric aspects but also socio-cultural aspects, certain features and characteristics of the culture. In the teaching learning process, language and culture are considered interconnected. It can be stated that a language is a part of culture and a culture is a part of a language. Language cannot be taught without reference to cultural context. By understanding socio-cultural contexts, learners can encounter the factors of cultural differences. English teachers should acknowledge English expressions to the learners in English cultural contexts. In order to help teacher in assisting learners to overcome cultural problems, some activities recommended are role plays, simulation, games, readings, watching English films, inviting native speaker to attend a classroom, giving assignment to the learners to meet native speaker, and cross cultural gathering with expatriates. Thus, the English learners are expected to be able to use English as a means of communication in various spoken and written English contexts. Moreover, the development of the learnersâ cultural awareness leads them to more critical thinking. The learners are more creative and have a sensitivity of culture in producing English utterances. In other words, the learners should have made efforts how to use English communicatively. Pedagogical implication for teaching English as a foreign language should consider English cultural elements integrated in English teaching-learning activities in order to gain communicative competence. Regardless of different point of views, the aim of this study provides necessary information of cultural awareness for the English teachers and learners and that of teaching learning activities incorporating the target language and its culture. Keywords: Â cultural awareness, communicative competence, socio-cultural competence